All the Rage: How Small Groups are Really Educating Christian Adults Part Three: Anchoring Small Group Ministry Practice—Biblical Insights and Leadership Development - Rynsburger, Mary (Christian education journal, 2009)
This three-part series considers the current and widespread trend of church-based small groups for adult spiritual formation. It is proposed that a focus on relationships must be kept in balance with learning and application of biblical truth in order for greater spiritual growth to result. The mini-series appears in three parts: The first article (Spring 2008) assesses small group ministries for an understanding of the current state of its sometimes blemished practice. In addition, a review of Christian-oriented small group literature is included, as well as an annotated bibliography of non-Christian-oriented small group literature. The second article (Fall 2008) is intended to augment small group practice by adapting key educational insights from the academic disciplines of group dynamics, communication theory, and educational psychology. The third article (Spring 2009) anchors small group practice by delving into the unique spiritual aspects of learning and addresses the biblical/theological apologetic for the centrality of Scripture. Finally, suggested applications are given for small group leaders and trainers of leaders as to how adults may be more effectively stimulated to learn and grow through such group involvement.